2017
DOI: 10.1504/ijrapidm.2017.082156
|View full text |Cite
|
Sign up to set email alerts
|

3D sand printing for automotive mass production applications

Abstract: Abstract:Additive manufacturing (AM) of metallic products is seen by many to be commercially viable for only small and highly complex components, manufactured with difficult to machine materials using heat sintering process. In the automotive manufacturing sector, metal hard tooling is often required to produce mass produced components, and the tools are typically bespoke, large in size, inflexible and complex. Conventionally these tools have either been machined from solid billets or near-net-shape cast and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…More binder may need to be added to achieve adequate strength. Such conclusions were reached by the authors of [24,27], who clearly indicate that the reason for the inferior surface quality of castings for the production of which 3D-printed cores were used is directly linked to excess binder. The authors of [1,[32][33][34], on the other hand, demonstrated the significant role of correct printing parameter settings, such as printing speed or the pressure of the newly applied sand layer, in reducing core porosity, which plays a decisive role in shaping a technologically important parameter-permeability.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…More binder may need to be added to achieve adequate strength. Such conclusions were reached by the authors of [24,27], who clearly indicate that the reason for the inferior surface quality of castings for the production of which 3D-printed cores were used is directly linked to excess binder. The authors of [1,[32][33][34], on the other hand, demonstrated the significant role of correct printing parameter settings, such as printing speed or the pressure of the newly applied sand layer, in reducing core porosity, which plays a decisive role in shaping a technologically important parameter-permeability.…”
Section: Introductionmentioning
confidence: 91%
“…The manufacture of molds and cores using 3D sand printing is of great interest, as evidenced by the growing number of publications devoted to the subject [23][24][25][26]. One of the most important advantages is the virtually unlimited possibilities regarding the shape of cores, as well as the high precision of printing.…”
Section: Introductionmentioning
confidence: 99%